Penerapan UI/UX Design pada Website Pet Care Berbasis Metode Design Thinking - Hudzaifah, Ahmad; Maulana, Reza (Jurnal Informatika Terpadu, 2025)
The Pet Care website prototype was developed using the Design Thinking method, selected for its user-centered approach increating innovative and effective solutions. The design process included stages of empathizing with users to understand theirneeds, defining problems, generating ideas, prototyping, and testing. The website is designed to facilitate easier access to petcare services while delivering a user-friendly and engaging experience. The results show an improvement in interaction qualityand ease of access to both information and services. Usability testing indicated that 94.6% of UI/UX elements functionedeffectively and met user expectations.